2020
DOI: 10.3390/s20174670
|View full text |Cite
|
Sign up to set email alerts
|

An IoT Smart Rodent Bait Station System Utilizing Computer Vision

Abstract: Across the world billions of dollars of damage are attributed to rodents, resulting in them being classified collectively as the biggest animal pest in the world. At a commercial scale most pest control companies employ the labour intensive approach of deploying and manually monitoring rodenticide bait stations. In this paper was present, RatSpy, a visual, low-power bait station monitoring system which wirelessly reports both on bait station levels and intruders entering the bait station. The smart bait statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Considering the rodent monitoring application, there is limited rodent control research on using IoT technology in recent years. One of the most common traditional approaches is placing bait stations [47,48], which may contain poisons that could harm pets and even people. In 2019, a low-power remote monitoring system was proposed to transmit data on bait and battery [47].…”
Section: Related Applications With Lora Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the rodent monitoring application, there is limited rodent control research on using IoT technology in recent years. One of the most common traditional approaches is placing bait stations [47,48], which may contain poisons that could harm pets and even people. In 2019, a low-power remote monitoring system was proposed to transmit data on bait and battery [47].…”
Section: Related Applications With Lora Technologymentioning
confidence: 99%
“…In 2019, a low-power remote monitoring system was proposed to transmit data on bait and battery [47]. In 2020, [48] presented a low-power bait station monitoring system Bait combined with computer vision, which can wirelessly report data from bait stations. To ensure the sustainability of the Earth, rodent infestation prevention should be implemented using non-toxic approaches that allow for no delay.…”
Section: Related Applications With Lora Technologymentioning
confidence: 99%
“…With the technological advances in computer science and engineering, designing automated toxin delivery devices specific to target species is now achievable (Meek et al 2020;Moseby et al 2020;Ross et al 2020;Corva et al 2022). We aimed to provide a reliable means of automatically replenishing baits while minimising undesirable bait loss (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…An Internet of Things (IoT)-based rodent infestation monitoring system is reported in [ 10 ], where the authors utilized sensor-based and vision-based algorithms for rodent monitoring. Ross et al reported the development of a smart rodent monitoring system called that uses computer vision and IoT for inspection within a rodent bait station [ 11 , 12 ]. Sowmika et al discuss a method of rodent detection in farmlands, where a PIR sensor is used to detect the motion of rodents within a range of ten meters, and sensor data collected are pushed to the cloud for enabling remote monitoring [ 13 ].…”
Section: Introductionmentioning
confidence: 99%